2004
DOI: 10.1002/kin.10186
|View full text |Cite
|
Sign up to set email alerts
|

Reduction kinetics of ceria surface by hydrogen

Abstract: Powdered cerium dioxide (ceria, CeO 2 ) as compressed, sintered pellets, of porosity 16.4% and density 5.99 g cm −3 , were treated in hydrogen flow at 1 atm and various temperatures to effect reduction. The electrical conductivity was measured in situ during the reduction process. The conductivity increased continuously during the hydrogen treatment because of the creation of anion vacancies and accompanying small polaron electrons. The conductivitytime relationship exhibits three distinct regions indicated as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
(31 reference statements)
1
7
1
Order By: Relevance
“…Chemical compatibility with 10 mol-% Y 2 O 3 stabilised ZrO 2 (YSZ) and Ce 0.9 Gd 0.1 O 1.9 (CGO) electrolytes in wet H 2 were evaluated in the temperature range of 800-1,000°C using PXRD and EDX. The area specific polarisation resistance of the investigated CMO was found to be higher than those of other ceria and zirconia anodes, and ASPR activation energy was found to be comparable to that of other electrodes reported in the literature [53][54][55][56][57][58][59]. and Tools (RTI) (cat.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Chemical compatibility with 10 mol-% Y 2 O 3 stabilised ZrO 2 (YSZ) and Ce 0.9 Gd 0.1 O 1.9 (CGO) electrolytes in wet H 2 were evaluated in the temperature range of 800-1,000°C using PXRD and EDX. The area specific polarisation resistance of the investigated CMO was found to be higher than those of other ceria and zirconia anodes, and ASPR activation energy was found to be comparable to that of other electrodes reported in the literature [53][54][55][56][57][58][59]. and Tools (RTI) (cat.…”
Section: Resultssupporting
confidence: 75%
“…Table 1 shows the lattice parameters of as-prepared and wet H 2 treated CMO samples. The increase in lattice parameter for reduced ceria is well known, and is believed to be due to oxygen vacancy formation [54][55][56][57][58] and simultaneous formation of polarons [56,59]. However, in the present study, we found no significant change in the lattice parameters in air and wet H 2 at 800°C which may be due to loss of interstitial oxygen atoms in CMO.…”
Section: Chemical Stability Of Cmo In H 2 and Wet Chcontrasting
confidence: 82%
“…The thermodynamic calculations show that such a process is expected within the CGO and, supported by the thermodynamic analysis, the three regions shown in Figure are attributed to the three phases of ceria. These results compare well with measurements of the electrical conductivity of cerium dioxide during reduction made by Al-Madfa et al for which three regions were observed . These first results are certainly encouraging as they show that the real time method, combined with accurate measurement of the surface temperature using the peak position, could be employed widely to understand the dynamics of phase stability and formation of unwanted phase under different experimental conditions highly complementary to thermodynamic calculations.…”
Section: Resultsmentioning
confidence: 99%
“…1 spectroscopy in order to explore for example the spin properties of novel oxide interfaces, 2-7 or of spin functional surfaces, [8][9][10][11][12][13][14][15][16] or to unravel details of the reactions taking place at the surface of catalysts [17][18][19][20][21][22][23][24][25][26][27] requires ever greater resolution and sensitivity. This implies the use of ever greater applied fields, which require in turn sample irradiation frequencies in the sub-THz range.…”
Section: Improving Electron Spin Resonance (Esr)mentioning
confidence: 99%